An Overview of CSIR Libraries as Knowledge Resource Centres: Issues and Trends - Verma, R.K.; Kalra, Jaya (DESIDOC Journal of Library & Information Technology, 2015)
A survey of CSIR libraries attached to the 38 laboratories and 3 CSIR units has been made with the main objective of reviewing the current status of the same. For this purpose, the data on infrastructure, resources, and the services provided by the libraries were collected using questionnaire in e-form. It is observed that the libraries are at varying levels and status in terms of infrastructural facilities vis-a-vis status of library staff. Keeping in view the manual guidelines issued by the CSIR during 2008, which renamed libraries as Knowledge Resource Centres, a few emerging issues like website and content development, knowledge management initiatives, institutional repositories have been discussed. A description of some possible future trends, e.g., implementation of knowledge management concepts, use of mobile devices, and changing user behaviours and expectations have also been touched upon. An overview of status, issues and possible trends for CSIR libraries ultimately points out the major responsibility of the librarians which covers the challenge of how to survive and sustain their position as one of the important and crucial stakeholders in the process of S&T information dissemination. It is concluded that the librarians have come out with more and more knowledge products in this competitive information society by making continuous efforts to develop their skills. This may include implementing the various techniques, and methods related to KM aspects including evaluation of websites for streamlining information organisation and content development. By adopting this strategy only libraries would be recognised as knowledge resource centres in true sense.